Pengaruh work-life balance terhadap kinerja karyawan melalui komitmen organisasi - Shinta Windika Putri; Agus Frianto (Jurnal Ilmu Manajemen, 2023)
Employee performance is an important thing that the company must consider because the employee's performance is expected to improve the company's quality as a whole. Several factors that can affect employee performance are work-life balance and organizational commitment. This study aims to analyze the effect of work-life balance on employee performance through organizational commitment. This research is a type of quantitative research. The sampling technique used is the total sample technique, with the total number of employees of Bank X as many as 46 people. Data was collected using a questionnaire measured by a Likert scale. The statistical analysis of this research is PLS (Partial Least Square) with SmartPLS 3.0 software. The results of this study indicate that work-life balance has a positive and significant effect on employee performance. Work-life balance has a positive and significant impact on organizational commitment. Organizational commitment has a positive and significant impact on employee performance. Organizational commitment has successfully mediated the relationship between work-life balance and employee performance. The implications based on the research results show that companies must pay attention to time management for employees to create a good work-life balance. In addition, organizational commitment must also be considered because it can impact employee performance.